Pengaruh Zat Adiktif Dan Batu Bata Merah Sebagai Substitusi Pasir Terhadap Kuat Lentur Dan Tekan Beton Dengan Perendaman Air Laut Dan Air Tawar - Mappa, Muh Hijrawansa; Setiawan, Arman; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Concrete is a material that is easy to shape and mold according to the needs of building concrete structures and is able to withstand compressive loads very well, has a relatively long life, is able to withstand high temperatures, and low maintenance costs. From the results of the design of a normal concrete mixture f'c 20 Mpa obtained the composition of cement mix: 379.63 kg/m3, crushed stone 1-2: 998.70 kg/m3, sand: 671.48 kg/m3, and water: 225.18 kg/m3. The compressive strength of normal concrete is higher than the compressive strength of 9% red brick variation concrete and 0% Silicafume by 21.2 Mpa. The more use of red bricks in the concrete mixture, the lower the compressive strength. This suggests that as silicafume variations increase with seawater immersion and freshwater the resulting compressive strength value increases. The compressive strength value with freshwater immersion is higher in seawater. The addition of red bricks to the concrete mixture has increased in bending strength with freshwater soaking compared to seawater soaking and normal concrete. As silicafume variations increase with seawater and freshwater immersion the resulting bending strength value increases as much as in compressive strength.